Sagot :
We can determine from here that the common difference is -5 since:
[tex]a_2-a_1=2-7=-5[/tex]
so:
[tex]n= \frac{a_n-a_1}{d} +1= \frac{-18-7}{-5} +1= 6[/tex]
[tex]a_2-a_1=2-7=-5[/tex]
so:
[tex]n= \frac{a_n-a_1}{d} +1= \frac{-18-7}{-5} +1= 6[/tex]
The formula for the arithmetic sequence:
[tex]a_n=a_1+(n-1)d[/tex]
Find the common difference:
2-7=-5
Substitute -18 as [tex]a_n[/tex]
-18=7-5(n-1)
Distribute
-18=7-5n+5
Add like terms
-18=5n+12
Subtract both sides by 12
-30=-5n
Divide both sides by -5
n=6
Hope this helps =)
[tex]a_n=a_1+(n-1)d[/tex]
Find the common difference:
2-7=-5
Substitute -18 as [tex]a_n[/tex]
-18=7-5(n-1)
Distribute
-18=7-5n+5
Add like terms
-18=5n+12
Subtract both sides by 12
-30=-5n
Divide both sides by -5
n=6
Hope this helps =)